GAYA KEPEMIMPINAN DEMOKRATIS MEMODERASI PENGARUH ASIMETRI INFORMASI DAN BUDAYA ORGANISASI PADA SENJANGAN ANGGARAN - Lestiana, Linda; sari, Maria M ratna (E-Jurnal Akuntansi, 2017)
The purpose of this study is to determine the leadership style of moderating influence of asymmetry of information and organizational culture on budgetary slack in work units (SKPD) the city of Denpasar. This study was conducted on 34 SKPD contained in Denpasar city administration. The population of this research is the Head of the fields / part, Head of the sub-section and section chief at the Regional Work Units Denpasar. The sampling method used in this study is saturated samples. The data collection is done by using a survey method using a questionnaire. Data analysis technique used isMR A . Based on the results of analysis show that information asymmetry positive influence on budgetary slack. Organizational culture negative influence on budgetary slack. Democratic leadership style was not able to moderate the influence of asymmetry of information on budgetary slack. However able to moderate the influence of organizational culture on budgetary slack.
Keywords: Democratic Leadership Style; Information Asymmetry; Organizational Culture; budgetary slack